Photometric Study And Orbital Solution For Some Newly Discovered Eclipsing Binary Systems - Alenazi, M. S.; Elkhateeb, M. M. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We present an orbital solution and light curve analysis for the three newly discovered W UMa systems: V0757 And, IK Lyn, and V0996 Per by means of first CCD observations. New times of minima were estimated and the observed light curves were analyzed using the most recent version of Wilson-Devinney modeling code (WD code) based on model atmospheres by Kurucz. The accepted models revealed some parameters describing the orbit of each system which showed that the primary components in all systems are massive and hotter than the secondary components. The spectral types of the systems' components were adopted and the locations of the systems on the theoretical mass-luminosity and mass-radius relations revealed a good fit for all the systems components except the secondary components of the systems V0996 Per and V0757 And are located above the TAMS track. Представлено орбитальное решение и анализ кривых блеска для трех недавно открытых систем W UMa: V0757 And, IK Lyn и V0996 Per с помощью первых ПЗС-наблюдений. Были оценены новые времена минимумов и проанализированы наблюдаемые кривые блеска с использованием самой последней версии кода моделирования Уилсона-Девинни (код WD), основанного на моделях атмосфер Куруца. Принятые модели позволили выявить некоторые параметры, описывающие орбиту каждой системы, которые показали, что первичные компоненты во всех системах массивнее и горячее, чем вторичные компоненты. Спектральные классы компонентов систем и расположение систем по теоретическим соотношениям масса- светимость и масса-радиус показали хорошее соответствие для всех компонентов систем, кроме вторичных компонентов систем V0996 Per и V0757 And, расположенных выше последовательности TAMS.
Keywords: Astrophysics